Fatores críticos de sucesso na captação de recursos junto a agências internacionais de fomento à pesquisa e desenvolvimento: um estudo na área de saúde no Brasil - Salviati, Raquel Cristina Martins (2021)
Advances in health research demand specific and appropriate infrastructure, highvalue equipment, and specialized personnel, making no Public Research Institute (PRI) wholly independent or completely controlling the conditions of its existence. Thus, a large part of the PRIs funding is external, and their survival occurs with organizational and institutional adjustments, closely related to the adaptation to the adversities of the Research and Development (R&D) system. This adaptation is critical in countries with a limited supply of resources and diversity in funding sources. It is essential that PRIs know the funding programs available in these countries and each funding system’s rules, including international ones. In this context, this thesis aims to determine the critical success factors related to the R&D management of PRIs in the health area in the search for fomentation from international agencies. For the survey and definition of the theoretical framework, two Systematic Literature Mapping studies were carried out, supported by the Prisma recommendation, culminating in the proposition of a conceptual-theoretical model through inductive content analysis. Primary data were collected from online questionnaires answered by PRIs managers and researchers from these institutions who obtained funding from international funding agencies. Data analysis was performed by comparing it with the proposed theoretical-conceptual model and, as a result, 15 critical success factors were established, gathered into five groups: 1) Administration and monitoring of the need for R&D resources; 2) Monitoring of the development agency scenario and search for opportunities; 3) Adequacy of project proposals to the criteria of agencies; 4) stimulating and enhancing the recognition and reputation of the researcher and ICT and; 5) Development and implementation of R&D Management and Coordination strategies in PRIs. These factors are interrelated and should be considered when seeking funding from international R&D funding agencies. Understanding these critical success factors, in addition to enriching the scientific literature, can therefore contribute to the implementation of management practices in PRIs, aimed at diversifying their funding sources.